Indonesian Advocates’ Success Fee Agreements: Policies and Challenges - Dananjaya, Putu Bagus; Perbawa, I Ketut Sukawati Lanang Putra; Buriev , Yulchiboy Khudaynazarovich (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
The regulation of success fee agreements in Indonesia remains largely interpretative, characterized by the predominance of contractual freedom and the absence of explicit normative limits. This study examines the policies and challenges surrounding success fee arrangements between advocates and clients, focusing on the interplay between legal certainty, ethical boundaries, and professional standards. Using a normative juridical method that integrates statutory, conceptual, and comparative approaches, the research explores the disharmony between the Indonesian Advocates Law, the Indonesian Advocates Code of Ethics, and the professional guidelines issued by PERADI. The findings reveal that, while success fees provide flexibility and proportional compensation based on case outcomes, the lack of uniform quantitative standards and the blurred distinction between lawful success fees and prohibited quota litis practices have created legal uncertainty. Furthermore, the ethical prohibition against remuneration solely based on case results limits the enforceability of such agreements. A comparative analysis with the English system, particularly its Conditional Fee Agreements and Damages Based Agreements, highlights the importance of transparent regulation, proportional limits, and ethical oversight to balance professional autonomy with client protection. Accordingly, this study recommends a reformulation of Indonesia’s policy framework to harmonize ethical norms and positive law, ensuring that success fee agreements promote fairness, professionalism, and legal certainty within the advocacy practice.